Space-time modeling of heuristic problems for decision-making systems - Glinenko, Larisa (Видавництво Львівської політехніки, 2012)
Mathematical model of heuristic problems satisfying demands to models in ihtellectual systems is developed on basis on space-time structure model of a function.
Keywords: model; heuristic problem; conflict